PENGARUH FINANCING TO DEPOSIT RATIO (FDR) TERHADAP RETURN ON ASSET (ROA) PADA BANK SYARIAH ANAK PERUSAHAAN BUMN DI INDONESIA PERIODE 2011-2019 - Agustin Tri Lestari (WADIAH, 2021)
This study aims to analyze the effect of Financing to Deposit Ratio (FDR)on Return On Asset (ROA) in Islamic banks, a subsidiary of BUMN. Thisresearch is classified as a descriptive quantitative research. This researchwas conducted at the Sharia Bank Subsidiaries of BUMN, namely BankSyariah Mandiri, Bank BRI Syariah, and Bank BNI Syariah. The data usedin this study are secondary data obtained from the quarterly financialreports for the 2011-2019 period. Data collection techniques throughliterature and documentation. The analysis method used in this research isSimple Regression Analysis, Descriptive Test, and Classical AssumptionTest. As for the hypothesis test used is the t test and the test ofdetermination (R2).From the results of the analysis, it shows that the FDRcondition is in the quite good category. Then for the ROA condition it is inthe quite good category. Based on several tests that have been carriedout, it is known that FDR does not have a significant effect on ROA. This isevidenced in the results of the Determination Test which shows that thesize of the FDR ratio is only able to affect the ROA ratio by 0.005 or 0.5%.This means that FDR has a very weak influence in increasing the ROA ofSharia Banks in BUMN Subsidiaries. This is due to other factors that moreinfluence ROA, such as CAR, NPF, and BOPO.